Dietary galactose exacerbates autoimmune neuroinflammation via advanced glycation end product-mediated neurodegeneration - Haase, Stefanie; Kuhbandner, Kristina; Mühleck, Florian; Gisevius, Barbara; Freudenstein, David; Hirschberg, Sarah; Lee, De-Hyung; Kuerten, Stefanie; Gold, Ralf; Haghikia, Aiden; Linker, Ralf A. (Frontiers in Immunology, 2024)
Background: Recent studies provide increasing evidence for a relevant role of lifestyle factors including diet in the pathogenesis of neuroinflammatory diseases such as multiple sclerosis (MS). While the intake of saturated fatty acids and elevated salt worsen the disease outcome in the experimental model of MS by enhanced inflammatory but diminished regulatory immunological processes, sugars as additional prominent components in our daily diet have only scarcely been investigated so far. Apart from glucose and fructose, galactose is a common sugar in the so-called Western diet. Methods: We investigated the effect of a galactose-rich diet during neuroinflammation using myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis (MOG-EAE) as a model disease. We investigated peripheral immune reactions and inflammatory infiltration by ex vivo flow cytometry analysis and performed histological staining of the spinal cord to analyze effects of galactose in the central nervous system (CNS). We analyzed the formation of advanced glycation end products (AGEs) by fluorescence measurements and investigated galactose as well as galactoseinduced AGEs in oligodendroglial cell cultures and induced pluripotent stem cell-derived primary neurons (iPNs). Results: Young mice fed a galactose-rich diet displayed exacerbated disease symptoms in the acute phase of EAE as well as impaired recovery in the chronic phase. Galactose did not affect peripheral immune reactions or inflammatory infiltration into the CNS, but resulted in increased demyelination, oligodendrocyte loss and enhanced neuro-axonal damage. Ex vivo analysis revealed an increased apoptosis of oligodendrocytes isolated from mice adapted on a galactose-rich diet. In vitro, treatment of cells with galactose neither impaired the maturation nor survival of oligodendroglial cells or iPNs.However, incubation of proteins with galactose in vitro led to the formation AGEs, that were increased in the spinal cord of EAE-diseased mice fed a galactose-rich diet. In oligodendroglial and neuronal cultures, treatment with galactose-induced AGEs promoted enhanced cell death compared to control treatment. Conclusion: These results imply that galactose-induced oligodendrocyte and myelin damage during neuroinflammation may be mediated by AGEs, thereby identifying galactose and its reactive products as potential dietary risk factors for neuroinflammatory diseases such as MS.